THE RESULTS OF SOCIAL CONSTRUCTION IN UZBEKISTAN IN THE LATE 30S OF THE TWENTIETH CENTURY - Feruza Rakhamanovna Isakova (Galaxy International Interdisciplinary Research Journal, 2022)
After the establishment of Soviet power by the end of the 30s of the twentieth century, great changes took place in the formation of the new Soviet intelligentsia in Uzbekistan. The process of its formation took place under the strict control of the state authorities, which pursued a policy of ideological Russification. However, despite this, Uzbekistan has formed its own national intelligentsia, which has made a significant contribution to the development of all aspects of public life.